Robot Dogs and the Paw Patrol - Ishaan Selby (Humanimalia)
This paper explores the cultural politics of the police dog by tracing the role of dogs in the fabrication and reproduction of an anthropocentric social order in line with the imperatives of racial capitalism. These imperatives are based on sorting forms of life in accordance with their proximity to a normative white humanity as part of a project of meeting capitalism’s shifting valorization requirements. I argue that such sorting manifests as both labourers compelled to work by the violence of policing and as populations rendered surplus and made to die through killing, confinement, or organized abandonment. The paper reads the historical use of police dogs against Black protesters from the Civil Rights Era to the present, the children’s television show PAW Patrol, and Israel’s use of robot dogs in its ethnic cleansing of the Gaza Strip as examples of policing as an operation of life sorting and as a manifestation of racial (bio)capitalism that makes use of the lively capacities and properties of dogs. The paper draws on work at the intersections of animal studies, Black studies, labour studies, and critical theories of settler colonialism (especially those focused on occupied Palestine) to argue for thinking together Black liberation, police abolition, Palestinian liberation, and animal liberation toward a project of mutual freedom for all life on a shared and finite world.